(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we initiate the study on 2-vertex covering of a graph. We characterize the 2-vertex covering sets in some special graphs, join and corona of two graphs, and we derive some bounds or formulas of the said parameter of each of these graphs.